Complement Receptor 2 Is Expressed in Neural Progenitor Cells and Regulates Adult Hippocampal Neurogenesis - Moriyama, Maiko (Society for Neuroscience, 2011)
Injury and inflammation are potent regulators of adult neurogenesis. As the complement system forms a key immune pathway that may also exert critical functions in neural development and neurodegeneration, we asked whether complement receptors regulate neurogenesis. We discovered that complement receptor 2 (CR2), classically known as a coreceptor of the B-lymphocyte antigen receptor, is expressed in adult neural progenitor cells (NPCs) of the dentate gyrus. Two of its ligands, C3d and interferon-α (IFN-α), inhibited proliferation of wild-type NPCs but not NPCs derived from mice lacking Cr2 (Cr2(−/−)), indicating functional Cr2 expression. Young and old Cr2(−/−) mice exhibited prominent increases in basal neurogenesis compared with wild-type littermates, whereas intracerebral injection of C3d resulted in fewer proliferating neuroblasts in wild-type than in Cr2(−/−) mice. We conclude that Cr2 regulates hippocampal neurogenesis and propose that increased C3d and IFN-α production associated with brain injury or viral infections may inhibit neurogenesis.